InterPoser: Visualizing Interpolated Movements for Bouldering Training - Shiro, Keisuke; Egawa, Kazme; Miyaki, Takashi; Rekimoto, Jun (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2019)
Bouldering is an urban form of rock climbing that requires precise and complex movement. Similarly to other sports, the simplest way to learn bouldering skill is to mimic professional's motion. However, ordinary beginner boulders cannot learn to coaches, so that they learn by themselves or tutorial videos. Even if they managed, bouldering has a communication difficulty between a trainee and a trainer, that is, climbers cannot mimic the trainer's movement in parallel. Accordingly, we considered a video feedback system would be useful for beginners and suggested InterPoser: a novel visualization system for intermediate motion between a beginner climber and a more experienced. InterPoser receives two videos of different subjects climbing the sample problem and generates an intermediate movement. In addition, this motion is transferred into realistic images of the climber. The proposed system is expected to support beginner to acquire more detailed observation and understanding of the motion.